Information management for innovation networks—an empirical study on the "who, what and how" in networked innovation. Issue 3 (June 2016) - Rehm, Sven-Volker; Goel, Lakshmi; Junglas, Iris
Highlights: Innovation networks are vital in advancing new product and service development for small and medium enterprises. Three principal challenges have to be overcome when forming innovation networks: building partnerships, integrating value contributions, and coordinating innovation processes. Information systems play a central role in tackling these three challenges. Information management must pay attention to managing the aspects of "who, what and how" in networked innovation. Abstract: Innovation networks are vital in advancing new product and service development. Particularly for small and medium-sized enterprises, partnering within innovation networks allows to enlarge innovation capabilities and to reach new markets. In order to create effective innovation networks, however, firms are required to adapt to the network. To do so, they must overcome three principal challenges: they need to build partnerships, integrate the partners' value contributions, and coordinate innovation processes. We followed three innovation networks over a three-year period and examined how they successfully used information systems (IS) to respond to these challenges. On the basis of their experiences we identify IS categories and measures that support setting up an information management for networked innovation. We explicate relevant tasks for managing the aspects of "who, what and how" in networked innovation.